Addition of Super Absorbent Polymer for Upgrading of Cement Quality in Iraqi Oil Wells - Ibrahim, Dhorgham Skban; Almahdawi, Faleh H. M. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
This study focuses on the use of an optimum amount of Sodium Polyacrylate (SP) for designing cement slurry with the high performance of rheological properties and displacement efficiency. A laboratory study has been carried out on the cement slurry which prepared with SP as superabsorbent polymer. SP has been providing an internal water source that helps in the hydration process, and curing and ultimately increases the cement strength. Also improves the cement performance by improving the cement stability. Several batches were prepared to determine the proper amount of SP to add it in the cement slurry. Also, we studied its effect on cement density, amount of free water in order to observe the rheological properties, and thickening time. Results indicate that the designed cement rheological properties are directly influenced by the shear rate and shear stress on the mix and pump of the cement with the increase of the SP concentration for the rheological improvement. Laboratory data are presented to highlight Polyacrylate’s positive effect on compressive strength, fluid loss control, and free water. This is an open access article under the CC BY-NC license https://creativecommons.org/licenses/by-nc/4.0/